Isotachophoretic determination of amino acids after their conversion to hydroxy acids - Kovářová, Michaela; Bartoš, Martin; Mikysek, Tomáš; Hloušková, Dana; Hyhlíková, Blanka; Vladyková, Jana (Springer, 2018)
In this article, determination of amino acids by capillary isotachophoresis based on their derivatization (van Slyke reaction) is presented. Hence, the suggested method deals with reaction of amino acids with nitrous acid forming corresponding hydroxy acids. This reaction was used in isotachophoretic analysis for the first time. Optimal conditions represented by electrolyte system for separation of hydroxy acids, 0.01 mol/dm(3) HCl, 0.05% hydroxyethyl cellulose, with beta-alanine (leading electrolyte of pH 3.6) and 0.01 mol/dm(3) valeric acid with sodium hydroxide (terminating electrolyte of pH 7.24), were chosen; furthermore, other critical details of the analysis are also described. Developed method brings original results and shows applicability on analysis of amino acids in relatively simple mixtures, especially in food supplements. [GRAPHICS] .
Izotachoforetické stanovení aminokyselin po jejich konverzi na hydroxykyseliny
Keywords: Aminoacid; Isotachophoresis; Determination; aminokyseliny; izotachoforéza; stanovení